2010
DOI: 10.3354/meps08583
|View full text |Cite
|
Sign up to set email alerts
|

The importance of attitude: the influence of behaviour on survival at an ontogenetic boundary

Abstract: Behavioural traits can strongly influence fitness and survival and are important mediators of life history trade-offs. This study explored the links between mortality trade-offs associated with fast growth during larval life and behaviour of individuals during an important life history transition. Longitudinal sampling of a cohort of damselfish settling on a reef at the end of their larval stage found that individuals with small otolith sizes at hatching and low otolith growth rates were selectively removed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 66 publications
(74 reference statements)
1
62
1
Order By: Relevance
“…Survival was monitored twice a day for 70 to 96 h after release. Previous tagging studies suggest that migration between patches or to the main reef is negligible [17,21,28]. In this study, there were no instances where two fish were found on a single patch reef.…”
Section: Methodsmentioning
confidence: 52%
See 4 more Smart Citations
“…Survival was monitored twice a day for 70 to 96 h after release. Previous tagging studies suggest that migration between patches or to the main reef is negligible [17,21,28]. In this study, there were no instances where two fish were found on a single patch reef.…”
Section: Methodsmentioning
confidence: 52%
“…Adults and juveniles occur in shallow lagoons, where they inhabit the reef edge or reef top associated with rubble. Larval duration is 16-21 days, with fish reaching 13-14 mm standard length (SL) at the end of the larval stage [17]. Fish can potentially disperse hundreds of kilometres from their natal location [18], and newly metamorphosed fish settle as solitary individuals into habitats with conspecific adults and sub-adults.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations